Plan de comunicación corporativa para la cooperativa de transporte río Peripa del cantón El Empalme, año 2015 - Muñoz Meza, Boris Heráclito (2016)
The present research on the "CORPORATE COMMUNICATIONS PLAN FOR TRANSPORTATION COOPERATIVE CANTON RIVER JUNCTION Peripa, 2015" has the main objective to analyze the situation in the cooperative now to seek new strategies to promote the viability of maintaining the service with efficiency in customers. The theoretical foundation on which this study is set on marketing studies, their development and communications, and service strategies, job performance of employees and the corporate communication plan with their respective conceptual framework that are part Additional variables specific research objectives. The methods used were scientific methods deductive, inductive and in which types of research employees are field research, literature and descriptive. Therefore the results of the investigation were made based on surveys and interviews to the President of the cooperative transport "Rio Peripa" The findings discussed were: The implementation of a communication plan is inescapable for transportation cooperative Peripa River, currently lacks the necessary publicity, causing decrease their market positioning. The internal administrative and service flaw originated imbalance in the organization and the partners feel concerned and unhappy about the current situation in the association. With their respective recommendations Implementation of the communication plan will improve the corporate image of the bus cooperative River Peripa Canton El Empalme, so it is necessary that Mr President and members take relevant and important decisions that contribute to new strategies strengthening marketing through advertising and customer service.